2009
DOI: 10.1002/jso.21368
|View full text |Cite
|
Sign up to set email alerts
|

A novel modification of double stapling technique in Billroth I anastomosis

Abstract: Although the double-stapling technique has been used as a safe procedure in gastroduodenostomy, creating anastomosis with a circular stapler on the linear stapler line can be vulnerable for anastomotic leakage and ischemia. Therefore, we tried to modify the double-stapling technique to avoid stapling on the staple line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In surgical procedure of subtotal gastrectomy, surgeons transect the distal stomach that is to be resected and complete the gastrojejunostomy with the linear stapler. After performing anastomosis by using stapler, suture line with stapling material is usually located in the lesser curvature side of the remnant stomach and around gastrojejunostomy site [ 12 , 13 ]. Therefore, performing ESD for the remnant stomach lesion around these sites is frequently technically demanding.…”
Section: Discussionmentioning
confidence: 99%
“…In surgical procedure of subtotal gastrectomy, surgeons transect the distal stomach that is to be resected and complete the gastrojejunostomy with the linear stapler. After performing anastomosis by using stapler, suture line with stapling material is usually located in the lesser curvature side of the remnant stomach and around gastrojejunostomy site [ 12 , 13 ]. Therefore, performing ESD for the remnant stomach lesion around these sites is frequently technically demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported manipulation of the stomach without prior resection of the mass containing portion of the distal stomach. 3,4 However, our technique allows us to confirm complete resection of the tumor as well as tumor-free margins by freezing the section prior to proceeding with the anastomosis. (2) By using the 25-mm circular stapler, the likelihood of traumatic injury to the jejunum would be less.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies including a randomized controlled trial supported his results,2324 and spleen preservation is now a standard procedure for total gastrectomy. He also developed new surgical techniques that can reduce anastomosis leakage after gastroduodenostomy 2526…”
Section: Development and Standardization Of Surgical Techniques For Gmentioning
confidence: 99%